2015
DOI: 10.1016/j.juro.2015.06.104
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Early Psychosocial Functioning of Parents of Children with Moderate to Severe Genital Ambiguity due to Disorders of Sex Development

Abstract: Purpose We examined the psychosocial characteristics of parents of children with disorders of sex development at early presentation to a disorders of sex development clinic. Parental anxiety, depression, quality of life, illness uncertainty and posttraumatic stress symptoms were assessed. Additionally we evaluated the relationship of assigned child gender to parental outcomes. Materials and Methods A total of 51 parents of children with ambiguous or atypical genitalia were recruited from 7 centers specializi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 17 publications
1
55
0
Order By: Relevance
“…Stress levels for both mothers and fathers of children with DSD are similar to those reported by parents of children with cancer soon after learning of their child’s diagnosis [7]. Mothers report more stress if their young child with atypical appearing genitalia has not yet received genitoplasty [8], and both mothers and fathers report reduced stress 6 months after their young child with ambiguous genitalia received surgery to “normalize” their appearance [9].…”
Section: Anxiety Depression Stress and Qol In Parents Of Young Chilmentioning
confidence: 79%
See 1 more Smart Citation
“…Stress levels for both mothers and fathers of children with DSD are similar to those reported by parents of children with cancer soon after learning of their child’s diagnosis [7]. Mothers report more stress if their young child with atypical appearing genitalia has not yet received genitoplasty [8], and both mothers and fathers report reduced stress 6 months after their young child with ambiguous genitalia received surgery to “normalize” their appearance [9].…”
Section: Anxiety Depression Stress and Qol In Parents Of Young Chilmentioning
confidence: 79%
“…Increased stress relates to higher levels of anxiety and greater depression in parents of children with DSD [10], and these factors are associated with decreased mental health QoL for these caregivers [7]. Currently, researchers are attempting to understand how to best support caregivers of children with DSD with resources and education to reduce their anxiety and depression in an effort to ultimately improve their QoL.…”
Section: Anxiety Depression Stress and Qol In Parents Of Young Chilmentioning
confidence: 99%
“…In the face of these challenges, the majority of families navigating DSD demonstrate improved coping after initial postdiagnosis distress [3], characteristic of resilience [4]. However, some affected individuals and their parents report significant distress related to aspects of the DSD experiences, such as coping with healthcare experiences, stigma concerns, and confusion related to diagnosis and decision-making [3, 5-10]. …”
Section: Introductionmentioning
confidence: 99%
“…In general, follow-up studies have indicated dissatisfaction with overall sex life and sexual function [3][4][5]98], as well as with binary gender [99], negative body image [100], social isolation [101], and experiencing normalizing surgery as dilemmatic [102]. Also, children are described by decreased health-related QoL, whereas parents by lower levels of emotional well-being and lower QoL mental health scores than among community samples [103]. In line with the psychological aspects related to DSD described previously, early and constant contact with a MHP should be available for children/adolescent with DSD and their families in order to have a good QoL by promoting competence and experienced efficacy in both parents and children with DSD.…”
Section: Qol Of Patients Affected By Dsd and Their Parentsmentioning
confidence: 99%